2019
DOI: 10.1146/annurev-cancerbio-030518-055653
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells in Cancer Immunotherapy

Abstract: Natural killer (NK) cells have evolved to complement T and B cells in host defense against pathogens and cancer. They recognize infected cells and tumors using a sophisticated array of activating, costimulatory, and inhibitory receptors that are expressed on NK cell subsets to create extensive functional diversity. NK cells can be targeted to kill with exquisite antigen specificity by antibody-dependent cellular cytotoxicity. NK and T cells share many of the costimulatory and inhibitory receptors that are curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
113
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 204 publications
(204 reference statements)
0
113
1
1
Order By: Relevance
“…Therefore, CD16-directed bispecific (eg, CD16 and CD19) or trispecific (eg, CD16 and two tumor antigens CD19 and CD22 or one tumor antigen and an IL-15 linker) antibodies or scFv have been developed. 37 Although primarily functioning as innate immune cells, studies have shown that NK cells might also have a role in antigen-specific immunological memory. In a Rag2-deficient model of hapten-induced contact hypersensitivity, NK cell-mediated hapten-specific response was detected for at least a month after priming.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CD16-directed bispecific (eg, CD16 and CD19) or trispecific (eg, CD16 and two tumor antigens CD19 and CD22 or one tumor antigen and an IL-15 linker) antibodies or scFv have been developed. 37 Although primarily functioning as innate immune cells, studies have shown that NK cells might also have a role in antigen-specific immunological memory. In a Rag2-deficient model of hapten-induced contact hypersensitivity, NK cell-mediated hapten-specific response was detected for at least a month after priming.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to BiTEs, NK-targeting bi-(BiKEs) and tri-specific killer engagers (TriKEs) have been developed [78]. These are composed of small molecules containing the variable portion (V H and V L ) of an antibody linked to one (BiKE) or two (TriKE) variable portions from other antibodies of different specificity.…”
Section: Recent Findings Related To Immunotherapy Against Multiple Mymentioning
confidence: 99%
“…Although NK cells can recognize a broad range of cancer cells in vitro, the contribution of their activity to immunotherapy for solid tumors has just begun to be appreciated (5,6). Pre-clinical data have shown that NK cell depletion increases tumor growth (7).…”
Section: Introductionmentioning
confidence: 99%